Question: Find the equation of the line joining \(\displaystyle (0-3)\), \(\displaystyle (-5,0)\)

I encountered a problem when finding the gradient. y2-y1/x2-x1

If \(\displaystyle (0, -3)\) is the x1,y1

\(\displaystyle 0-(-3)/-5-0\) = \(\displaystyle 3/-5\) = \(\displaystyle -0.6\)

If \(\displaystyle (0, -3)\) is the x2,y2

\(\displaystyle -3-0/0-5\) = \(\displaystyle -3/-5\) = \(\displaystyle 0.6\)

Where am I wrong? [Solved]

My workings for this question:

Gradient = y2-y1/x2-x1

\(\displaystyle =\) \(\displaystyle (-3-0)/(0-(-5)\)

\(\displaystyle =\) \(\displaystyle -3/5\)

\(\displaystyle =\)\(\displaystyle -0.6\)

\(\displaystyle 0=-0.6(-5)+b\)

\(\displaystyle 0=3+b\)

\(\displaystyle 0-3=3-3+b\)

\(\displaystyle -3=b\)

Therefore, \(\displaystyle y=-0.6x-3\)

Is my answer correct?

I encountered a problem when finding the gradient. y2-y1/x2-x1

If \(\displaystyle (0, -3)\) is the x1,y1

\(\displaystyle 0-(-3)/-5-0\) = \(\displaystyle 3/-5\) = \(\displaystyle -0.6\)

If \(\displaystyle (0, -3)\) is the x2,y2

\(\displaystyle -3-0/0-5\) = \(\displaystyle -3/-5\) = \(\displaystyle 0.6\)

Where am I wrong? [Solved]

My workings for this question:

Gradient = y2-y1/x2-x1

\(\displaystyle =\) \(\displaystyle (-3-0)/(0-(-5)\)

\(\displaystyle =\) \(\displaystyle -3/5\)

\(\displaystyle =\)\(\displaystyle -0.6\)

\(\displaystyle 0=-0.6(-5)+b\)

\(\displaystyle 0=3+b\)

\(\displaystyle 0-3=3-3+b\)

\(\displaystyle -3=b\)

Therefore, \(\displaystyle y=-0.6x-3\)

Is my answer correct?

Last edited: